2016
DOI: 10.1159/000452256
|View full text |Cite
|
Sign up to set email alerts
|

From Common to Rare Variants: The Genetic Component of Alzheimer Disease

Abstract: Alzheimer disease (AD) is a remarkable example of genetic heterogeneity. Extremely rare variants in the APP, PSEN1, or PSEN2 genes, or duplications of the APP gene cause autosomal dominant forms, generally with complete penetrance by the age of 65 years. Nonautosomal dominant forms are considered as a complex disorder with a high genetic component, whatever the age of onset. Although genetically heterogeneous, AD is defined by the same neuropathological criteria in all configurations. According to the amyloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 117 publications
1
31
0
Order By: Relevance
“…Consistent with the downregulation of IL-10 receptor signaling in Csf1r +/microglia, its downstream signaling mediator, Stat3 and several IL-10 transcriptional targets (Ddit4, Nfil3, Tsc22d3) (Ip et al, 2017, Lang et al, 2002, Berrebi et al, 2003, Hoppstadter et al, 2015 were also downregulated ( Fig 5B, F). Other potentially relevant downregulated genes encode transcripts associated with Alzheimer's disease (Sorl1) (Nicolas et al, 2016), leukodystrophy (Abcd1 and its downstream mediator of pathology, Ch25h) (Gong et al, 2017, Jang et al, 2016 and the CSF-2 target gene Pkch, encoding protein kinase Cη, a regulator of lipid metabolism and suppressor of NO production by macrophages (Torisu et al, 2016, Ozawa et al, 2016 ( Fig 5B). Pathway analysis revealed that the transcriptomic changes associated with Csf1r heterozygosity are consistent with activation of the RhoGDI signaling and LXR/RXR pathways ( Fig.…”
Section: Gene Expression Changes In Csf1r +/-Microglia Suggest a Malamentioning
confidence: 99%
“…Consistent with the downregulation of IL-10 receptor signaling in Csf1r +/microglia, its downstream signaling mediator, Stat3 and several IL-10 transcriptional targets (Ddit4, Nfil3, Tsc22d3) (Ip et al, 2017, Lang et al, 2002, Berrebi et al, 2003, Hoppstadter et al, 2015 were also downregulated ( Fig 5B, F). Other potentially relevant downregulated genes encode transcripts associated with Alzheimer's disease (Sorl1) (Nicolas et al, 2016), leukodystrophy (Abcd1 and its downstream mediator of pathology, Ch25h) (Gong et al, 2017, Jang et al, 2016 and the CSF-2 target gene Pkch, encoding protein kinase Cη, a regulator of lipid metabolism and suppressor of NO production by macrophages (Torisu et al, 2016, Ozawa et al, 2016 ( Fig 5B). Pathway analysis revealed that the transcriptomic changes associated with Csf1r heterozygosity are consistent with activation of the RhoGDI signaling and LXR/RXR pathways ( Fig.…”
Section: Gene Expression Changes In Csf1r +/-Microglia Suggest a Malamentioning
confidence: 99%
“…Late‐onset AD accounts for more than 95% of all AD cases and is caused by a complex underlying genetic architecture. To date, over 40 GWASs and meta‐analyses have identified a few hundred genes and single nucleotide polymorphisms; these include variants in apolipoprotein E ( APOE ) among other notable gene candidates [228]. In contrast to late‐onset AD, early onset AD is caused by highly penetrant variants located primarily in three genes with minimotif functions, APP (located at 21q21.2), presenilin 1 ( PSEN1 , located at 14q24.3), and presenilin 2 ( PSEN2 , located at 1q42.13) [226].…”
Section: Genetics and Epigenetics Of Minimotifs In Ndsmentioning
confidence: 99%
“…In contrast, sequencing studies have been successful at identifying more moderately to highly penetrant contributions to disease by examining rare variation. Successes in Alzheimer’s disease (AD) include ABCA7 , SORL1 , and TREM2 (reviewed in 7 ). Similar successes for the amyotrophic lateral sclerosis (ALS)-FTD spectrum include TBK1 8 , MFSD8 9 , DPP6 , UNC13A , and HLA-DQA2 10 .…”
Section: Introductionmentioning
confidence: 99%